2011
DOI: 10.1038/jhg.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-141 confers resistance to cisplatin-induced apoptosis by targeting YAP1 in human esophageal squamous cell carcinoma

Abstract: MicroRNAs (miRNAs) are endogenous non-coding RNAs that function as negative regulators of gene expression. Alterations in miRNA expression have been shown to affect tumor growth and response to chemotherapy. In this study, we explored the possible role of miRNAs in cisplatin resistance in esophageal squamous cell carcinoma (ESCC). First we assessed the sensitivity of nine human ESCC cell lines (KYSE series) to cisplatin using an in vitro cell viability assay, and then we compared the miRNA profiles of the cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 41 publications
1
64
0
1
Order By: Relevance
“…Recently, a study showed that downregulated miR-141 may confer cisplatin resistance in esophageal squamous cell carcinoma (19). Moreover, miR-141 modulates cisplatin sensivitity in ovarian cancer cells (20 The present study is the first to report that increased miR-141 expression was associated with acquired docetaxel resistance in vitro and changes in miR-141 expression modulated response to docetaxel in BC cells, at least in part by targeting the eukaryotic translation initiation factor 4E (EIF4E).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Recently, a study showed that downregulated miR-141 may confer cisplatin resistance in esophageal squamous cell carcinoma (19). Moreover, miR-141 modulates cisplatin sensivitity in ovarian cancer cells (20 The present study is the first to report that increased miR-141 expression was associated with acquired docetaxel resistance in vitro and changes in miR-141 expression modulated response to docetaxel in BC cells, at least in part by targeting the eukaryotic translation initiation factor 4E (EIF4E).…”
Section: Introductionmentioning
confidence: 61%
“…All the above research reported that miR-141 not only to acts as a tumor suppressor, but also as an oncogene. Equally important, Imanaka et al highlighted an important regulatory role for miR-141 in the development of cisplatin resistance in esophageal squamous cell carcinoma (19). Furthermore, the miR-141-mediated regulation of kEAP1 has a crucial role in the cellular response to cisplatin in ovarian cancer cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Again, some researchers reported that miR-451 regulates P-gp expression in doxorubicin-resistant MCF-7 cells (Kovalchuk et al, 2008). There is other evidence on miRNA and anticancer agents, such as tamoxifen (Cittelly et al, 2010), cisplatin (Bian et al, 2011;Imanaka et al, 2011), 5-fluorouracil (Shah et al, 2011;Valeri et al, 2010) and other anticancer drugs (Giovannetti et al, 2011).…”
Section: Mirna Expression and Drugsmentioning
confidence: 99%
“…miR-141 was the most highly expressed in the cisplatin-resistant ESCC cell lines and the cell viability was significantly increased following cisplatin treatment. The target of miR-141 is YAP1, which is an apoptosis-inducing gene in DNA-damaging agents (85). miR-296 and miR-27a were overexpressed in EC and the knockdown of miR-296 and miR-27a was capable of increasing sensitivity to both P-glycoproteinrelated and P-glycoprotein-non-related drugs, in turn promoting ADR-induced apoptosis in EC cells (86,87).…”
Section: The Role Of Mirnas In Treatment Of Ecmentioning
confidence: 99%